Effect of heat stress and planting date on yield, grain quality and fertilizer uptake of rice cultivars (Oryza sativa L.) - Karbalaei Aghamolki, Mohammad Taghi (2016)
In the first experiment, high temperature tolerance, in terms of transplanting dates (1st May, 21st May and 10th June) was tested on six Iranian rice cultivars. The response of rice cultivars and transplanting dates for the morphological, and yield components showed the crop sown on 1st and 21st May had better growth and yield components which resulted higher grain yield (6625 kg ha") of Neda cultivar. The second experiment was glass house conducted to evaluate the effects of high temperature (38±2°C) stress and normal temperature (32±2°C) on seven rice cultivars. The results showed the greater weight of 1000 grains (26.97 g) observed in Neda grown in normal condition. The maximum grain yield (51.3 g pot") was noted in MR219 planted in normal condition. In third experiment, the effect of normal and heat stress temperatures were tested on four rice cultivars (Fajr, Hashemi and Hovaze as exotic and MR219 as indigenous). The main effects of heat stress and growth stage were significant in all parameters except on effective tillers. The lowest grain yield per pot was observed in Hashemi (6.8 g pot") at flowering stage during heat stress condition and the highest was found in MR219 (42- 45d g pot") during normal condition. In conclusion, the major reason for yield reduction of all cultivars was enhancement of sterile and aborted spikelets numbers when plants exposed to heat stress during booting and flowering phases. The last experiment was conducted on the rice cultivars from previous experiment to evaluate the effect of normal temperature and heat stress using Potassium fertilizer, nitrogen, and Meister-20 (polymer coated urea). The grain yield was significantly higher (25.9 g pot") in the plants grown in normal condition and fertilized with Meister-20 at 160 kg N ha". In the heat stress condition, the grain yield ranged between 15.3 to 17.9 g pot:' in the N fertilized plants which is also considered satisfactory as compared to unfertilized plants in the heat stress condition.